2021
DOI: 10.1186/s12886-021-01817-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of ocular complications among children undergoing nephrotic syndrome treatment in a resource-limited setting

Abstract: Background Nephrotic syndrome is the most common glomerulopathy among children aged 2–18 years and high dose corticosteroids are the backbone of its management. Potentially blinding ocular complications often result from nephrotic syndrome and/or its treatment. We conducted a study to determine the prevalence and predictors of ocular complications among children undergoing nephrotic syndrome treatment at Mulago National Referral Hospital. Methods T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
(27 reference statements)
2
6
2
Order By: Relevance
“…The least frequent manifestations were Epiblepharon in 4 patients (8.30%) and ptosis in 3 (6.3%) of patients. Our study is in agreement with Nakubulwa et al (7) who reported that a total of 80/100 (80%) participants had ocular complications. Seventy-one (71%) patients had hypertrichosis of the eye lashes, 56 (56%) had refractive errors, 37% had allergic conjunctivitis and 10% had blepharitis and bacterial conjunctivitis.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The least frequent manifestations were Epiblepharon in 4 patients (8.30%) and ptosis in 3 (6.3%) of patients. Our study is in agreement with Nakubulwa et al (7) who reported that a total of 80/100 (80%) participants had ocular complications. Seventy-one (71%) patients had hypertrichosis of the eye lashes, 56 (56%) had refractive errors, 37% had allergic conjunctivitis and 10% had blepharitis and bacterial conjunctivitis.…”
Section: Resultssupporting
confidence: 93%
“…Hypertrichosis in our study was found in 25 patients (52.1%). This is in agreement with Nakubulwa et al (7) who found that hypertrichosis was the most frequent ocular complication in 70 patients (70%). Through an unidentified mechanism, systemic steroids promote facial hypertrichosis.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The clinical efficacy of patients was evaluated according to the “Standards for Diagnosis and Efficacy of TCM Diseases and Syndromes” [ 21 ] and changes in clinical signs, 24 h urine protein quantification, and recovery of ALB indicators. Significantly effective means the obvious improvement of TCM symptoms and clinical signs and 24 h urine protein quantification ≤ 1.0 g, ALB ≥ 35 g/L.…”
Section: Methodsmentioning
confidence: 99%